PENGARUH SALES PROMOTION, PERSONAL SELLING, DAN VISUAL MERCHANDISING TERHADAP PERILAKU IMPULSE BUYING KONSUMEN MATAHARI DEPARTMENT STORE PsX PALEMBANG - Apria Sari; Ahmad Widad; Aslamia Rosa (JEMBATAN, 2015)
This research aimed the impacts of promotion strategy on consumer impulse buying behavior at Matahari Department Store in PsX Palembang. The variables used in this research were sales promotion variable (X1), personal selling (X2), visual merchandising (X3), and impulse buying behavior (Y). This research was descriptive causal research. The population of this research were all of people who had ever done impulsive purchasing at Matahari Department Store in PsX Palembang, at least three times in a year. The number of respondents were 100 people. The analysis result showed that sales promotion variable (X1), personal selling (X2), and visual merchandising (X3) simultaneously had significant influence on consumer impulse buying behavior. The results of t test showed that sales promotion variable (X1), and visual merchandising variable (X3) had significant influence on consumer impulse buying behavior, whereas personal selling variable (X2) had not significant influence on consumer impulse buying behavior. The most dominant variable that influence consumer impulse buying behavior was visual merchandising variable. Overall, the sales promotion variable (X1), personal selling (X2), and visual merchandising (X3) had contributed 21.8% to impulse buying behavior at Matahari Department Store in PsX Palembang consumers and another 78.2% had influenced by the other variables.Keyword: Sales Promotion, Personal Selling, Visual merchandising, Impulse Buying